Replacement of cardiotoxic aminopiperidine linker with piperazine moiety reduces cardiotoxicity? Mycobacterium tuberculosis novel bacterial topoisomerase inhibitors. Issue 1 (1st January 2016) - Bobesh, Karyakulam Andrews; Renuka, Janupally; Srilakshmi, Rudraraju Reshma; Yellanki, Swapna; Kulkarni, Pushkar; Yogeeswari, Perumal; Sriram, Dharmarajan
Graphical abstract: This kind of compounds retains good potency and showed reduced cardiotoxicity compared to aminopiperidines. Abstract: Recently numerous non-fluoroquinolone-based bacterial type II topoisomerase inhibitors from both the GyrA and GyrB classes have been reported as antibacterial agents. Inhibitors of the GyrA class include aminopiperidine-based novel bacterial type II topoisomerase inhibitors (NBTIs). However, inhibition of the cardiac ion channel remains a serious liability for the aminopiperidine based NBTIs. In this paper we replaced central aminopiperidine linker with piperazine moiety and tested for its biological activity. We developed a series of twenty four compounds with a piperazine linker 1-(2-(piperazin-1-yl)ethyl)-1, 5-naphthyridin-2(1 H )-one, by following a multistep protocol. Among them compound 4-(2-(7-methoxy-2-oxo-1, 5-naphthyridin-1(2 H )-yl)ethyl)- N -(4-nitrophenyl)piperazine-1-carboxamide (11 ) was the most promising inhibitor with Mycobacterium tuberculosis (MTB) DNA gyrase enzyme supercoiling IC50 of 0.29 ± 0.22 μM, with a good MTB MIC of 3.45 μM. These kind of compounds retains good potency and showed reduced cardiotoxicity compared to aminopiperidines.